(untitled) (Seminar_BG, 2025)
Park Badelema in the town of Asenovgrad is another Bulgarian case in which economic, political and public interests collide over development pressures and efforts to preserve urban green space. The local ecological resources, conservation practices, and educational initiatives at the urban park, town, and municipality levels, created and developed in the past, are the foundation of Asenovgrad’s contemporary biocultural heritage. In the current situation, the conflict was created after a decision by the Municipal Council to build on a part of the park, which caused public reactions and at least the temporary suspension of these plans. In the absence of political will, the future of the Badelema Ecopark, for the creation of which all the ecological preconditions are in place, will depend largely on whether civic mobilization remains a declining defensive response or develops into sustained support for expert planning and implementation. In addition to presenting the case, this text seeks to contribute to a broader public and political debate on the future of Badelema Ecopark by engaging expert capacity and encouraging informed civic participation. References Cranz, G., & Michael, B. (2004). Defining the Sustainable Park: A Fifth Model for Urban Parks. Landscape Journal, 23(2), 102-120. https://doi.org/10.3368/lj.23.2.102. Daskalov, H. (1978). Moyat zhivot takav, kakavto go vidyah. Rodopi, 6. Dzhambov, A., Stoyanova, V., & Dimitrova, D. (2017). Gradsko ozelenyavane i obshtestveno zdrave – savremenni nauchni postizheniya. Sotsialna meditsina, 1, 13–18. http://dx.doi.org/10.14748/sm.v0i1.4080 Fioretti, C., Pertoldi, M., Busti, M. & Van Heerden, S. (eds). (2020). Handbook of Sustainable Urban Development Strategies. Luxembourg: Publications Office of the European Union. https://territorial.ec.europa.eu/sustainable-development/strategies/handbook-sud/ [19.12.2025] Ganeva-Raycheva, V. (2021). Biokulturno nasledstvo – da svarzhem biologichnoto i kulturnoto raznoobrazie (kulturni politiki i praktiki). Byuletin „Nasledstvo BG“ – Nauchni izvestiya, 1, 57–63. Hirt, S. (2013). Whatever Happened to the (Post)socialist City?. Cities 32(1), S29-S38. https://doi.org/10.1016/j.cities.2013.04.010. Ignatov, V. (2013). Ot Stanimaka do Shtatite. Prezhivelitsi. Plovdiv: Fast print book. Kalinkov, K. (2010). Funktsionalniya podhod v ustroystvoto i razvitieto na gradovete. Nauka i ikonomika, 82, 7–64. Kaneva, R. (2024). Zelenoto nasledstvo na balgarskite gradove. In I. Kabakov (ed.), Kulturnata pamet na grada (pp. 120–147). Sofia: Universitetsko izdatelstvo „Sv. Kliment Ohridski“. Krastev, A. (2004). Obshtinskite saveti i kmetove na Asenovgrad. Asenovgrad: Ekobelan. Lefebre, H. (1996). Writings on Cities. Oxford: Blackwell. Markov, K. (2013). 130 godini Lovno-ribarsko druzhestvo „Sokol“ – Asenovgrad. Asenovgrad: Ekobelan. Naskova, P., & Georgieva, P. (2025). Savremenni predizvikatelstva pred ozelenyavaneto v gradska sreda. E-Journal VFU, 23: 1–12. Petrov, P. (2019). Rekonstruktsiya i obnovyavane na sgradi i gradski prostranstva [avtoreferat na disertatsionen trud, Nov balgarski universitet]. https://eprints.nbu.bg/id/eprint/4139/1/арх.%20Петър%20Петров%20-%20Avtoreferat.pdf. [20.12.2025]. Petrov, Ts., & Petrova, E. (1984). Uchebna ekologichna baza. Obshtinski naroden savet – Asenovgrad, Okrazhna stantsiya na mladite agrobiolozi – Plovdiv, OU „Hr. Botev“ – Asenovgrad. Shishkova, D. (2020). Struktura na konflikta v sluchaya Bedechka. Fizicheski i kognitivni izmereniya na sotsialnata mrezha. Sotsiologicheski problemi, 52(2), 624–647. Slaev, A., & Hirt., S. (2022). Planning, Pluralism, Markets: Experiences from Post-Socialist Varna, Planning Theory & Practice, 23(3), 461-475, https://doi.org/10.1080/14649357.2022.2061774. Stanchev, H. (2003). Ah, tezi asenovgradchani. Asenovgrad: Ekobelan. Steward, J. (1955). Theory of Culture Change: The Methodology of Multilinear Evolution. Champaign: University of Illinois Press. Tsenkova, S. (2006). Beyond transitions: Understanding urban change in post-socialist cities. In S. Tsenkova & Z. Nedović-Budić (eds.), The Urban Mosaic of Post-Socialist Europe. Contributions to Economics. Physica-Verlag HD. https://doi.org/10.1007/3-7908-1727-9_2. Vasileva, A., & Kaleva, E. (2013). Balgarskiyat postsotsialisticheski grad: transformatsiya na publichnoto prostranstvo, globalizatsiya i identichnost. Kritika i humanizam, 42(1-2), 95–109. Venkov, N. (2012). Grazhdanskoto obshtestvo i Zhenskiya pazar. Sofia: Izsledovatelski tsentar za sotsialni nauki.